Spatial distribution of public secondary education services in the main cities of Basra Governorate (a study in the geography of cities) - AbduAl Jabbar, Ammae; Ismael Othman AL Rashid , Assist. Prof. Dr.Osama (Basra studies journal, 2022)
The study found a wide spatial disparity in the distribution of secondary education services (intermediate, middle, secondary, vocational) in the main cities of Basra Governorate. It is not sufficient to meet the actual needs of the residents of the main cities in the governorate for the year 2020, as the total number of government secondary education services (intermediate, preparatory, secondary, vocational) reached (236, 94, 54, 19) secondary schools, and occupied an area of ​​(833,000) , 324770, 190,188, and 100,300 m 2) respectively, so it is required, according to the approved demographic and cadastral standards, to provide a number of government secondary education services (intermediate, preparatory, secondary, and vocational), which number (504, 504, 504, 102) secondary schools. With a total area of ​​1,888,000, 940,000, 540,000, and 1,900,000 square meters, respectively, and according to the future perspective and for the next ten years (2030), a number of secondary education services (intermediate, preparatory, secondary, and vocational) are required, totaling (2078). ) secondary school For both sexes, with a total area of ​​19,500,000 square meters, in accordance with the approved demographic and cadastral standards, in order for secondary education services to reach good efficiency at the present and to guarantee the right of future generations.